Analisis Faktor-Faktor yang Memengaruhi Pertumbuhan Laba LPD di Kota Denpasar Tahun 2014-2017 - Putra, Aditya Pratama; Dwija Putri, I G.A.M. Asri (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
This study aims to obtain empirical evidence from the effect of cash turnover rates, credit growth rates, savings growth rates, growth rates on labor costs on profit growth. This research was conducted in Denpasar City LPD with the number of samples used by 34 LPDs. The research method used is non probability sampling, namely purposive sampling technique. The analysis technique used is multiple linear analysis techniques. The results show the cash turnover rate and credit growth rate have a positive effect on LPD profit growth in Denpasar City in 2014-2017, while the savings growth rate and the level of labor costs negatively affect LPD profit growth in Denpasar City in 2014-2017 Keywords: Cash turnover, credit growth, savings growth, labor cost growth, profit growth